[Historical buildings] - Norton, Noel, P. (Trinidad Photopraghers Ltd., 2010)
Description printed on the back of the postcard: "Trinidad and Tobago, West Indies: The new flag of Trinidad and Tobago flies over Whitehall, office of the Prime Minister of Trinidad an Tobago, in Port of Spain. Whitehall faces the 200 acre Queen's Park Savannah, site of a race track and numerous cricket and soccer fields." The Stollmeyers Castle, which was constructed in the early 20th century is also featured in the postcard.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Mansions--Trinidad and Tobago; [1970]; Whitehall (Port of Spain); Magnificent Seven, The (Port of Spain); Stollmeyer's Castle (Port of Spain); Queen's Park Savannah